(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The plants are directly affected by environmental factors such as water stress, temperature, radiation, among others. These factors affect not only the vegetative organs, but also reproductive structures and may cause damage to plants agriculturally exploited. Physalis peruviana L. is a species of commercial interest belongs to the Solanaceae family, preferably grown under shade, which still features restricted to small cultivation areas in Brazil. Given the need for shading culture presented by this study aimed to characterize the pollen grain species for future applications in breeding programs and the influence of shading nets on the external morphology of the pollen grains of this species. The study was conducted at the Federal University of Lavras, where three replicates of two plants were grown in full sun and under shading nets in white, blue, red and black colors. The pollen of flowers in anthesis was collected, processed and photographed by scanning electron microscopy (SEM) electron microscopy. The polar diameter, equatorial diameter and area were measured in ten pollen grains. The results showed that pollen grains of P. peruviana are isopoloares, radial, of prolate-spheroidal format and medium size. Also there was an increase in the pollen grain area when grown in white shading net and full sun.